Surgical treatment of orthokeratinized odontogenic cyst in maxillary sinus: Case report in pediatric patient - Albuquerque-Neto, Antonio Dionízio; Cesconetto, Lorenzzo De Angelli; Cerqueira, Daniel Assunçao; Araujo, André Victor Alves; Oliveira, Vinicius Dantas; Oliveira, Eder Magno Ferreira (Journal of Oral Diagnosis, 2018)
The orthokeratinized odontogenic cyst is a rare developmental cyst that affects the jaws. Since 2017 it has been classified as an independent entity of odontogenic keratocyst, since it presents differences in its biological behavior, histopathological aspects, as well as less aggressiveness and potential for recurrence. It affects young individuals, with predomi- nance for the masculine gender. Their behavior is not aggressive, but can reach large proportions. The present case reported, in a male patient, 9 years old, with an expansive osteolytic process of large proportions was observed, taking all the extension of the left maxillary sinus. The patient was submitted to enucleation of the lesion under general anesthesia, is being followed up without signs of relapse.